ICTV Virus Taxonomy Profile: Peribunyaviridae - Hughes, Holly R; Adkins, Scott; Alkhovskiy, Sergey; Beer, Martin; Blair, Carol; Calisher, Charles H; Drebot, Mike; Lambert, Amy J; de Souza, William Marciel; Marklewitz, Marco; Nunes, Márcio R T; Shí 石晓宏, Xiǎohóng; et al. (Journal of general virology, 2020)
Peribunyaviruses are enveloped and possess three distinct, single-stranded, negative-sense RNA segments comprising 11.2-12.5 kb in total. The family includes globally distributed viruses in the genera , , and . Most viruses are maintained in geographically-restricted vertebrate-arthropod transmission cycles that can include transovarial transmission from arthropod dam to offspring. Others are arthropod-specific. Arthropods can be persistently infected. Human infection occurs through blood feeding by an infected vector arthropod. Infections can result in a diversity of human and veterinary clinical outcomes in a strain-specific manner. Segment reassortment is evident between some peribunyaviruses. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the taxonomy of the family , which is available at ictv.global/report/peribunyaviridae.